MuSK antibody-positive, seronegative myasthenia gravis in Korea. - Lee, J; Sung, J; Cho, J; Oh, D; Kim, H; Park, J; Lee, K; Choi, Y; Vincent, A (2006)
Several reports from Western countries suggest differences in the clinical features of patients with muscle specific kinase (MuSK) antibody-positive and -negative seronegative myasthenia gravis (MG). We performed the first survey in Korea of MuSK antibodies, studying 23 patients with acetylcholine receptor (AChR)-antibody seronegative MG. MuSK antibodies were present in 4 (26.7%) of 15 generalized seronegative MG patients and none of 8 ocular seronegative MG patients. All four MuSK positive patients were females, with pharyngeal and respiratory muscle weakness, and required immunosuppressive treatment. However, overall disease severity and age at onset was similar to that of MuSK-negative MG and treatment responses were equally good.